Relationships among environmental literacy, locus of control, and future orientation of STEM students - Gatan, Princes Raymunda G.; Yangco, Rosanelia T.; Monterola, Sheryl Lyn C.; Oyzon, Maria Vanessa P. Lusung; Guerrero, Charlaine G. (Quezon City College of Education, University of the Philippines Diliman, 2019)
This study reports on the status and correlations of the locus of control (LOC), future orientation (FO), and environmental literacy (EL) of Science Technology, Engineering, and Mathematics (STEM) students (N = 512) in Quezon City. The student's locus of control was measured using the Internal Environment Locus of Control (INELOC) Tool. Recycling Attitude had the highest mean among its four dimensions, Activism and Advocate got a mean of 5.74 and 5.54, respectively. Both were below the average mean of 5.86. The results implied that most of the respondents believed that through recycling, they could improve or mitigate best the worsening condition of the environment and natural resources. On the other hand, Consideration of Future Consequences (CFC) Scale was used to measure the student's inclination to future orientation, and results showed that STEM students were inclined more to consider distant outcomes or consequences of their actions (M = 3.10) rather than focusing on meeting their immediate needs (M = 2.41). Meanwhile, the Environmental Literacy Test (ELT) results showed a relatively low rate of 56.26% The relationships among the STEM students' LOC, FO, and EL all yielded significant results. The relationship between LOC and EL revealed a weak negative relationship, r (510) = -.093 ; the relationship between FO and EL obtained weak positive relationship, r (510) = .206; lastly, the relationship between LOC and FO was found to be positive and weak, r (510) = .236. The STEM students' high academic achievement, their mindset that humans do not have full control over nature's action, their personal convenience and personal benefit, among others, might have contributed to this result.
Thesis
Includes bibliographical references (pages 87-94)
Keywords: Environmental education -- Philippines -- Quezon City